2017
DOI: 10.1002/slct.201701213
|View full text |Cite
|
Sign up to set email alerts
|

Refining the Structural Features of Chromones as Selective MAO‐B Inhibitors: Exploration of Combined Pharmacophore‐Based 3D‐QSAR and Quantum Chemical Studies

Abstract: Synthetic chromones are considered as a validated target of the inhibition of monoamine oxidase‐B and its relationship to various neurodegenerative diseases is increasing. Herein described is pharmacophore generation and atom‐based 3D‐QSAR analysis of previously reported chromone based MAO−B inhibitors in order to get insight into their structural requirements responsible for high affinity. The best four‐point pharmacophore model with five features AAHRR‐3, two hydrogen bond acceptor (A),one hydrophobic groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 36 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…MAO‐B inhibition blocks the catabolism of dopamine (DA) and, thus, increases endogenous dopamine levels, [ 8 ] whereas increased MAO‐B activity has been shown to be associated with the generation of reactive astrocytes leading to synaptic dysfunction and impaired cognitive function in the AD brain. [ 9 ] Furthermore, recent studies have shown MAO‐B mediated γ‐aminobutyric acid (GABA) production is linked to pathological pathways in AD and that suppressing GABA synthesis by inhibiting MAO‐B improves synaptic plasticity and reduces reactive astrocyte numbers in the AD brain.…”
Section: Introductionmentioning
confidence: 99%
“…MAO‐B inhibition blocks the catabolism of dopamine (DA) and, thus, increases endogenous dopamine levels, [ 8 ] whereas increased MAO‐B activity has been shown to be associated with the generation of reactive astrocytes leading to synaptic dysfunction and impaired cognitive function in the AD brain. [ 9 ] Furthermore, recent studies have shown MAO‐B mediated γ‐aminobutyric acid (GABA) production is linked to pathological pathways in AD and that suppressing GABA synthesis by inhibiting MAO‐B improves synaptic plasticity and reduces reactive astrocyte numbers in the AD brain.…”
Section: Introductionmentioning
confidence: 99%
“…MAO-B inhibitors have drawn considerable attention, and a variety of MAO-B inhibitors are developed. , Selegiline, rasagiline, and safinamide are often used alone or in combination with levodopa for the treatment of PD in clinics . In addition, recent examples have disclosed a variety of new MAO-B inhibitors, such as chromone, coumarin, chalcone, and N -containing heterocyclic compounds ,, (Figure ). In Borges’ studies, chromone derivatives were discovered as potential therapeutic compounds for relieving Parkinsonism, and these inhibitors exhibited promising activity against MAO-B. , Gobec et al found that geometric isomers of cis - and trans -1-propargyl-4-styrylpiperidines were potent MAO-B inhibitors and revealed the importance of their chirality for bioactivity .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The current scenario of PD therapy focuses on restoring the level of dopamine in the brain and thereby curtailing the motor symptoms. 9 This therapy is accelerated by the administration of dopamine precursors (L-DOPA), dopamine agonists, catechol-O-methyltransferase (COMT) and MAO-B inhibitors such as selegiline and rasagiline (highly selective and irreversible). 10 Molecules which have closer acetylcholinesterase (AChE) and MAO-B affinities are able to limit the neurotoxicity related to sources of ROS in age-related AD diseases.…”
Section: Introductionmentioning
confidence: 99%